Role of Learning and Growth Perspective in The Mediating Relation of Human Resource Function with Employee Champion: Evidence from The Small Medium Industries - Sapta Rini Widyawati; I Made Surya Prayoga; Tiksnayana Vipraprastha; I Wayan Gede Antok Setiawan Jodi; Ni Luh Gede Putu Purnawati; Pande Ketut Ribek (Universitas Pendidikan Ganesha, 2023)
Human resources (HR) is a key factor for achieving company competitive advantage, but research on the competitive advantage of HR is still little to do. As is known, the superiority of HR can be seen from the role of HR as an employee champion. This study aims to analyze the effect of the HR function on employee champions from the perspective of learning and growth as a mediating variable. The research sample consisted of 627 employees form 14 the small medium industries. The sample obtained was 82 employees. This research was conducted using questionnaires and interviews. In making the questionnaire used a scaling technique Likert to measure attitudes, income, and perceptions of people or groups of people about social phenomena that occur. The analytical tool used was SEM-PLS. The findings of the research result found that the HR function does not directly influence employee champions, but after incorporating the perspective of learning and growth as a mediating variable. It appears that the effect of the HR function on employee champions.